Tragedy and the limits of pessimism in ancient and modern realist political thought = Tragedia i granice pesymizmu w starożytnej i współczesnej realistycznej myśli politycznej - Humphries, Carl (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article explores the question of what we might discover about the nature and significance of contemporary forms of so-called "political realism" - particularly with regard to their relationship to pessimism - from a philosophical consideration of Ancient Greek tragedy on the one hand, and of such supposed ancient precursors of this way of thinking about ethical and/or political matters as Thucydides on the other.
Keywords: tragedia; pesymizm; political realism; tragedy; pessimism; realizm polityczny; Geuss, Raymond (filozof amerykański; 1946- ); Williams, Bernard Arthur Owen (filozof angielski; 1929-2003); Nietzsche, Friedrich Wilhelm (filozof niemiecki; 1844-1900); Wittgenstein, Ludwig Josef Johann (austriacki filozof; 1889-1951)